Agresja językowa w wypowiedziach Dmitrija Miedwiediewa - Kapela, Ewa (Przegląd Wschodnioeuropejski, 2026)
Verbal aggression is a common feature of political discourse, especially in the communication styles of Russian politicians such as Putin, Lavrov, and Zhirinovsky. Dmitry Medvedev, once known as a liberal and soft-spoken politician, became more aggressive after the Russian-Ukrainian war began in 2022. Hostile and aggressive messages started appearing regularly on Medvedev’s official social media accounts on Twitter and Telegram. The author of the article discusses the exponents of aggressive language in these messages, which often contain insults and threats. Furthermore, he points out potential reasons for Medvedev’s shift in rhetoric, attributing it to a deliberate change in his communication strategy.